Beyond Internships: Experiential Learning as a Tool for Emergency Management Education. Issue 1 (March 2019) - Penta, Samantha; Phillips, Samantha; Silver, Amber; Barrett, Emily
Experiential learning has emerged as a best practice in higher education and professional development programs. This article describes the 100-hour training requirement of an undergraduate degree program at a mid-sized public research university in the northeastern United States. The four tiers of the training program include: (1) foundational training, (2) professional development, (3) community engagement, and (4) concentration-specific training. Each tier is assigned a minimum number of hours that students must complete in order to meet the requirements of the program. The tiered structure focuses students' activity, ensuring that they engage in experiences that support the development of each of the content areas deemed important for student success as they transition from the academic to the professional realm. This paper illustrates a new way of integrating experiential learning into emergency management curriculum through a 100-hour training requirement, and demonstrates the benefits this type of educational experience can have for the students and the larger community. Beyond educational theory, external training opportunities professionalize students to the practical knowledge of the field and into a culture of continuous learning. It also offers the potential to serve the broader community, reflecting the value that higher education can have in their communities.